Peran Guru BK dalam Meningkatkan Keterampilan Belajar dan Motivasi Belajar Siswa - Satya Anggi Permana (Prodi Bimbingan dan Konseling Islam, 2020)
Learning skills and learning motivation must be in students to be successful and successful in learning, in this case, students need help and guidance to succeed in learning. One of those who play an important role in helping students is the school counselor. This type of research is qualitative research. The informants in this study were the principal, school counselor, subject teachers, homeroom teachers, and students. Data collection techniques in this study using observation, interview, and documentation techniques. Techniques for Guaranteeing Data Validity The research was carried out by means of a Credibility Test, Transferability Test, Dependability Test, and Confirmability Test. Data analysis techniques are carried out through the process of data reduction (data reduction), data display (data display), and conclusion (verification). The findings obtained in this study indicate that the role of school counseling in increasing student learning motivation is carried out well through the provision of information services. Meanwhile, the role of school counseling in improving student learning skills still needs to be improved by providing more intensive services with a combination of content mastery services, this is because there are still students who do not have good learning skills, and there is still a lack of service provision regarding learning skills that are felt by them. students, so that student learning outcomes are less than optimal. This study also reveals that